Application of Accounting: A Case Study at Delon Anas Notary Office - Ramadanis, R.; Fitri, Sri Adella; Wulan, Sari; Safitri, Ranaya; Vamia, V.; Hutria, Roza; Nofianti, Yola; Junaidi, Serlina (Manunggal Halim Jaya, 2024)
The application of accounting, especially in service companies, will of course be very useful. The aim is for a company to know how their financial flows are, so they can analyze the income and expenses they have made. The technique used in conducting this research was interviews conducted with the company. The results of this research indicate that the Delon Anas Notary Office does not carry out detailed and in-depth records using an accounting system. Instead, it only records a few transactions, such as income, but even that is not always recorded by the company.